SIGNIFIKANSI DESAIN KURIKULUM KKNI - Munir Munir; Kholid Kholid (Roqooba Journal of Islamic Education Management, 2022)
In its process, the National Education System (SNP) in the target quality of education serves leaning to positive values of social development in the community. This has become a necessity because the state has a great responsibility to direct the main concepts of education to a more mature and make the child the best education dimensionless generation of people in his life. This demand is undoubtedly switch to stakeholders in a more focused area that is College. In this framework the Universities largely responsible for providing instructional design good for students who join the educational units built. The studies on the formulation of the current curriculum design is necessarily directed to the contemporary frameworks formulated by the government. In terms of social values that want to be introduced to the world of education, should be realized by all practitioners in the development of education that education itself will be held accountable to the common values that thrive in the community. For this reason, contemporary social values that developed in the middle of the community would essentially become a major capital references must be embodied in education.